PERAN MEDIA PEMBELAJARAN KARTU GAMBAR DAN HURUF DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 (STUDI LITERATUR) - Habibah, Syahla; Maksum, Arifin; Aruwiyantoko, Anggit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early reading skills are essential for first-grade students as a foundation for their academic success. However, many students encounter difficulties in reading due to low motivation and less engaging teaching methods. This study reviews the role of game-based educational media, specifically picture and letter cards, in improving early reading skills. Using a literature review approach, relevant previous studies were analyzed. The findings indicate that picture and letter card media effectively enhance students’ reading abilities in a fun and interactive manner. These media help students visually recognize letters and words while increasing their motivation to learn. The teacher’s role as a facilitator is crucial in optimizing the use of these media. Validity and practicality tests show that the cards are suitable for classroom use. Therefore, game-based educational media are recommended as an effective strategy to help students overcome reading difficulties and build a strong foundation in early elementary reading.